(3JQLeI GdTGgfGeg ddaQOhSis - (3CHh EHQGgje GdaJM Hf Ydj Hf eMeO Hf CHj GdaJM, GdHfOGQj GdCUHgGfj,J (B643 (3g` s ((3Ydi Hf CMeO GdehUdi GdeYQha HGHf GdTgQSJGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JYWa QOGA GdcHQjGA s
(3BNQgG (B:s
(3GdMeO ddg QH GdYGdejf hUdhGJg Ydi SjOfG eMeO GdfHi GdCei s
(3cGf GdeDda MjkG SfI (B623s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B90 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs